Pre-pandemic climate and job satisfaction of nursing staff in an emergency service : Clima y satisfacción laboral prepandemia del personal de enfermería en un servicio de emergencia - Chávez Patilongo, Melina Liliana (2023)
Objective: To determine the relationship between work environment and job satisfaction of nursing staff in the emergency service of Hospital de Vitarte. Methods: Quantitative, correlational and cross-sectional research. The population and sample consisted of 70 members of the nursing staff of the emergency service. With the prior informed consent of each participant, two questionnaires validated in other studies were applied through a survey. Results: The participating nursing staff was mainly between 30 and 39 years old (50%), was female (62,9%), with the same number of professionals and technicians, with a slight predominance of contracted (51,4%) and had between 6 to 10 years of service. The dimensions of the work environment: self-realization (81,4%), work involvement (82,9%), supervision (82,9%) and communication (54,3%) were considered moderately favorable; working conditions were unfavorable (42,9%). The dimensions of satisfaction: physical conditions - materials (81,43%), administrative policies (72,86%) were unsatisfactory; while in social benefits – remuneration (87,14%), social relationships (47,14%), personal development (65,71%), task development (72,86%) and performance beyond the position (80%) were moderately satisfactory. The work environment was considered moderately favorable (48,57%) and job satisfaction was moderately satisfactory (42,86%). Conclusions: A statistically significant relationship was found between work environment and job satisfaction (p=0,023) in the nursing staff in the emergency service of the Hospital de Vitarte.